Lack of in-home piped water and reported consumption of sugar-sweetened beverages among adults in rural Alaska - Mosites, Emily; Seeman, Sara; Fenaughty, Andrea; Fink, Karol; Eichelberger, Laura; Holck, Peter; Thomas, Timothy K; Bruce, Michael G; Hennessy, Thomas W
Objective: To assess whether community water service is associated with the frequency of sugar-sweetened beverage (SSB) consumption, obesity, or perceived health status in rural Alaska Design: We examined the cross sectional associations between community water access and frequency of SSB consumption, body mass index categories, and perceived health status using data from the 2013 and 2015 Alaska Behavioral Risk Factor Surveillance System (BRFSS) Participants were categorized by zip code to “in-home piped water service” or “no in-home piped water service” based on water utility data We evaluated the univariable and multivariable (adjusting for age, household income and education) associations between water service and outcomes using log-linear survey-weighted generalized linear models Setting: Rural Alaska, USA Subjects: 887 adults, aged 25 years and older Results: In unadjusted models, participants without in-home water reported consuming SSBs more often than participants with in-home water (146, 95% CI 106, 200) After adjustment for potential confounders, the effect decreased but remained borderline significant (129, 95% CI 100, 167) Obesity was not significantly associated with water service but self-reported poor health was higher in those communities without in-home water (163, 95% CI 105-254) Conclusions: Not having access to in-home piped water could affect behaviors surrounding SSB consumption and general perception of health in rural Alaska CC999999/ImCDC/Intramural CDC HHS/United States